Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The wave equation in $\mathbb{R}^3$ , ie $u_{tt}-\Delta u=0 $ for $x\in \mathbb{R}^3, t>0 $

$u=g, u_t=h$ for $x\in \mathbb{R}^3, t=0$

Define an average: $U(x,r,t)= \frac {1}{|\partial B|} \int_{\partial B(x,r) }u(y,t)dS_y $ and similarly $G(x,r,t) =\frac {1}{|\partial B|} \int_{\partial B(x,r) }g(y)dS_y$


$H(x,r,t) =\frac {1}{|\partial B|} \int_{\partial B(x,r) }h(y)dS_y$

We fix $x \in R^n , n\ge2$ and suppose $u \in C^m(R^m\times \mathbb{R}_+$ for $m\ge2$

Claim : $U$ solves the following initial value problem . $U_{tt}-U_{rr}-\frac {(n-1)}{r} U_r=0, r>0, t>0$

$U=G, U_t=H , r>0, t=0$

Proof : $U_r =\frac {\partial}{\partial r}\frac {1}{|\partial B|} \int_{\partial B(x,r) }u(y,t)dS_y $. First derivative was easy for me to find but now My aim is to find $U_{rr}$ . There is another way of proving the claim without computation of second derivative . But i am looking forward to know how to differentiate it twice and many more times .

Any help will be appreciated.

share|cite|improve this question
up vote 4 down vote accepted

Since you didn't like my answer to your previous question, I'll give you the details. Let $B=B(0,1)$, and $y=x+r\,\xi$ with $\xi=1$. Then $$ U(x,r,t)=\frac{1}{|\partial B(x,r)|} \int_{\partial B(x,r)}u(y,t)\,dS_y=\frac{1}{|\partial B|} \int_{\partial B}u(x+r\,\xi,t)\,dS_\xi. $$ Derivating with respect to $r$ and using the divergence theorem $$\begin{align*} \frac{\partial U}{\partial r}&=\frac{1}{|\partial B|} \int_{\partial B}\xi\cdot\nabla_xu(x+r\,\xi,t)\,dS_\xi\\ &=\frac{r}{|B|} \int_{B}\Delta_xu(x+r\,\xi,t)\,d\xi\\ &=\frac{r^{1-n}}{|B|}\Delta_x \int_{B(x,r)}u(y,t)\,dy\\ &=r^{1-n}\Delta_x \int_0^r\rho^{n-1}U(x,\rho,t)\,d\rho. \end{align*}$$ From here it is easy to get $\partial^2 U/\partial r^2$, or better yet, $$ \frac{\partial}{\partial r}\Bigl(r^{n-1}\frac{\partial U}{\partial r}\Bigr)=r^{n-1}\Delta_xU(x,r,t). $$

share|cite|improve this answer
Thank you sir. Sorry for not liking your previous answer. – Theorem Jul 10 '12 at 19:15
Here basically we differentiate in a unit radius Ball in order to make sure that $u$ doesn't blowup right ? – Theorem Jul 10 '12 at 19:24

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.